2022
DOI: 10.3389/fonc.2022.912801
|View full text |Cite
|
Sign up to set email alerts
|

Liquid First Is “Solid” in Naïve Non-Small Cell Lung Cancer Patients: Faster Turnaround Time With High Concordance to Solid Next-Generation Sequencing

Abstract: PurposeMolecular profiling is crucial in naïve non-small cell lung cancer (NSCLC). While tissue-based analysis is challenged by turnaround time and scarcity of tissue, there is increasing demand for liquid biopsy. We aimed to analyze the use of upfront liquid biopsy as a molecular profiling approach.MethodsThis retrospective multicenter, non-interventional study compared findings and turnaround times of liquid vs. standard-of-care (SOC) tissue-biopsy molecular profiling. The study included naïve advanced NSCLC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…A prospective study in 282 patients with untreated metastatic NSCLC demonstrated that ctDNA analysis identified oncogenic variants on average 6 days before standard-of-care tissue genotyping, resulting in 9 versus 16 days of turnaround time (TAT) and thereby shortening the time to treatment significantly (median 18 days with liquid biopsy vs. 31 days with tumor tissue molecular profiling, p = 0.0008) [11]. These results were in line with a retrospective analysis, showing a median TAT in favor of LB [22,23]. The time between the molecular analysis request on a tissue biopsy and receiving the molecular report on the last biomarker was on average 21 (range 5-66) days.…”
Section: Diagnosis Of Early-stage Nsclcsupporting
confidence: 75%
“…A prospective study in 282 patients with untreated metastatic NSCLC demonstrated that ctDNA analysis identified oncogenic variants on average 6 days before standard-of-care tissue genotyping, resulting in 9 versus 16 days of turnaround time (TAT) and thereby shortening the time to treatment significantly (median 18 days with liquid biopsy vs. 31 days with tumor tissue molecular profiling, p = 0.0008) [11]. These results were in line with a retrospective analysis, showing a median TAT in favor of LB [22,23]. The time between the molecular analysis request on a tissue biopsy and receiving the molecular report on the last biomarker was on average 21 (range 5-66) days.…”
Section: Diagnosis Of Early-stage Nsclcsupporting
confidence: 75%
“…In terms of detection timelines, Sehayek et al compared the results and turnaround times of the molecular analysis of liquid and tissue biopsies, and found that liquid biopsies had consistent analytical results and shorter turnaround times. This means that liquid biopsy is feasible and accurate and can shorten the time required to diagnose NSCLC, especially when tumor tissues are scarce [ 41 ]. It is noteworthy that although NGS is widely touted as being more sensitive than qPCR, the available evidence suggests that all commonly used ctDNA detection techniques lack satisfactory sensitivity (e.g., qPCR, ddPCR, and NGS) [ 42 ].…”
Section: Plasma Ctdna-based Egfr Mutations Can Guide Targeted Therapy...mentioning
confidence: 99%